EFFECTS OF DECAMETHRIN AND PERMETHRIN ON THE BIOLOGY OF TWO COCCINELLID PREDATORS OF BLACK BEAN APHIDS - Vasquez, Erlinda A.; Bernardo , Emiliana N.; de Pedro, Lorenza B. (Annals of Tropical Research, 1987)
The two species of coccinellid predators (Chilomenes sexmaculata Fabr. and Coleophora inaequalis Fabr.) treated with decamethrin and permethrin showed slightly longer total developmental period, higher mortality rate and lower fecundity rate than the untreated ones, particularly C. inaequalis. No significant differences were found in percent egg hatchability and adult longevity. These results were observed only in the first generation where individuals were in direct contact with the insecticides but not in the second and succeeding generations. Data generally suggest that decamethrin is relatively safe to the two species of predators and that decamethrin-coccinellid combination could be recommended for black bean aphid control.